An experimental study on deformation analysis of an indented pipe via fringe projection profilometry and digital image correlation (2018)
We studied the surface displacement of a steel pipe during indentation via Fringe Projection Profilometry and 2D-Digital Image Correlation. Experimental results show that a 3D strain approximation is possible for comparison with numerical simulation. © 2018 The Author(s)